2007
DOI: 10.1007/bf02913329
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evaluation of some Ayurvedic preparations for correction of iron deficiency and anemia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Furthermore it was observed that this drug is effective in IDA among all age groups; pediatric, geriatrics and adult age groups. 6,12,13 Studies also reveal that this drug is well tolerated among the patients without any side effects and untoward effects compared to allopathic drug in one of the clinical trials. 12 One of the advantages of Ayurvedic preparations is that most of these drugs are administered with some vehicle which improves the efficacy of the parent drug and Punarnavadi Mandura is not an exception to this principle.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore it was observed that this drug is effective in IDA among all age groups; pediatric, geriatrics and adult age groups. 6,12,13 Studies also reveal that this drug is well tolerated among the patients without any side effects and untoward effects compared to allopathic drug in one of the clinical trials. 12 One of the advantages of Ayurvedic preparations is that most of these drugs are administered with some vehicle which improves the efficacy of the parent drug and Punarnavadi Mandura is not an exception to this principle.…”
Section: Discussionmentioning
confidence: 97%
“…Four studies were focused on the general population. [ 28 29 30 31 ] The Ayurvedic formulations studied in these four studies for their efficacy against IDA among general population include Navayasa Lauha , Punarnavadi Mandura , Dhatri Lauha , Pradarantaka Lauha , Sarva-Jvara-Hara Lauha , Brihat Yakrdari Lauha , Dadimadi Ghrita and Trikatrayadi Lauha . There are several explanations regarding the efficacy of Ayurvedic formulations in combating IDA in general population.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that a substantial portion of these Ayurvedic formulations contain organic matter that includes ascorbic acid, sugars, amino acids and organic acids, which cause better absorption of non-haem iron. [ 28 ] Furthermore, most of the Ayurvedic formulations are administered with some Anupana (vehicle) as in the case of Navayasa Lauha and Dhatri Lauha . These two formulations are administered with honey as Anupana which is a mixture of glucose and fructose and iron may combine with these sugars for absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger is another popular and widely used spice, but there exist no studies on the effect on nonheme iron uptake. Some authors suggest that ginger supplements may be beneficial for treatment of iron deficiency anemia when taken together with oral iron [ 63 , 64 ]. Until further studies are available, it is recommended that ginger should be used with moderacy in cooking foods, and ginger shots should be taken between meals.…”
Section: Methodsmentioning
confidence: 99%